Experiences of Thai Family Members of Patients with COVID-19 who Died in Intensive Care Units: A Phenomenological Study. - Keawsuttha, Watcharee; Chaiviboontham, Suchira; Pokpalagon, Piyawan (Pacific Rim International Journal of Nursing Research)
The COVID-19 pandemic exacerbated family distress during end-of-life care, especially in the intensive care unit. Resource constraints, limited hospital capacity, and increased economic strain hindered timely access to care while amplifying public fear and social isolation. While some studies have investigated family experiences across regions worldwide, little is known about these experiences within Asian cultural contexts, particularly in Southeast Asia. This qualitative study, grounded in Husserl's descriptive phenomenology, explored the experiences of Thai family members of patients with COVID-19 who died in intensive care units. Ten bereaved family members were recruited via snowball sampling on online platforms through a digital poster. Participants who met the eligibility criteria were video recorded during semi-structured online interviews. Data were analyzed using Colaizzi's seven-step phenomenological method, which provides a systematic process for moving from signif icant statements to formulated meanings, theme clusters, and an essential structure of the phenomenon. This approach enabled an in-depth understanding of Thai family members' lived experiences of the death and dying of a loved one to COVID-19 in the ICU, with rigor ensured in accordance with Guba and Lincoln's criteria. The analysis revealed six themes: 1) broken and disrupted communication; 2) living with uncertainty; 3) striving for involvement in patient care amid powerlessness; 4) eternal separation without a f inal goodbye; 5) disrupted funeral rituals and cultural practices; and 6) the journey toward healing after loss. The f indings underscore the need for clear communication, flexible family involvement supported by technology, and early mental health monitoring to strengthen family-centered and bereavement care in epidemic ICU contexts. Nurses play a key role in providing timely and consistent information, coordinating family engagement through digital contact, and offering compassionate support during restricted visitation. The f indings also highlight the importance of culturally and spiritually responsive nursing care aligned with Thai beliefs and practices. In addition, nurses should screen for psychological distress, provide bereavement support, and facilitate timely referrals to prevent complicated grief. Collectively, these implications support the development of flexible, family-centered nursing protocols that can be effectively implemented during pandemics and other infectious disease crises.